Exploring pre-pandemic patterns of vaccine decision-making with the 5C model: results from representative surveys in 2016 and 2018 - Sarah Eitze; Lisa Felgendreff; Nina Horstkötter; Linda Seefeld; Cornelia Betsch (BMC, 2024)
Abstract Background The 5C psychological antecedents of vaccination (Confidence, Complacency, Constraints, Calculation, and Collective Responsibility) facilitate understanding vaccination decisions in specific target groups as well as the general public's informational needs. This study aims to explain pre-pandemic vaccination behaviour (a) in general, (b) for specific vaccines such as influenza, and (c) for certain target groups (e.g. people over the age of 59 years, parents, healthcare workers), using the 5C model and sociodemographic variables. The intention to get an influenza vaccination was also analysed for target groups. Methods The 5C, self-reported vaccination behaviour and the intention to vaccinate were collected in two representative telephone surveys in Germany - one in 2016 (n1 = 5,012) and another in 2018 (n2 = 5,054). Parents, people over the age of 59 years, chronically ill people, people with a migratory background, pregnant women and healthcare workers were target groups. Results Overall, the 5C model had higher explanatory power than sociodemographic variables. The pattern of vaccine hesitancy slightly differed between vaccinations and target groups. Confidence in safety and effectiveness was always a significant predictor. Complacency (the underestimation of disease risks) and Constraints were significant predictors as well. Calculation (of risks and benefits) was important for influenza vaccination intentions. Conclusions This work builds an important benchmark for understanding potential changes in vaccine acceptance due to the pandemic. The benchmark can be used in research on potential effects of the pandemic on vaccination behaviours. Intervention designers can also use the results to understand specific audiences and their vaccination decisions.